Il diritto delle corti, la scienza e la tecnica: una tassonomia (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This essay aims to analyze how Italian Courts interact with scientific knowledge and technology. In particular the authors create a database where they try to classify a relevant number of judicial decisions according to the way they relate to science. This attempt is a proof of concept of a project that could be extended also to judicial decisions by foreign Courts.
Keywords: Science; Law; Transaction; Case law; Technology